Analysis of the factors affecting the effectiveness of character-based instructional video implementation to early childhood education in Padang - Abna Hidayati (Journal of Counseling and Educational Technology, 2018)
The education of character to the early childhood is essentially important because this stage is the golden stage to construct the child’s characters. However, the implementation of character education with instructional media encounters crucial problems especially applying the educational video. This study is to identify the factors which are influencing the effectiveness of character-based instructional video implementation to the early childhood education in Padang.This research conducts the quantitative approach with quasi-experiment. In addition, it involves 125 early childhood students in PAUD Adzkia II Tabing, Koto Tangah, Padang. Specifically, this study applies the purposive sampling categorised to Class A and Class B with 17 students in each. Both classes then were given discrete treatments to observe the ability of character education. The data was collected with questionnaires.The results concluded that there is significant distinction between the students who are treated with video and those who are only with uncomplicated pictures. Therefore, it is suggested that character-based educational video media is able to be implemented to increase the mastery of characters’ values to the early childhood students with supporting learning strategies.